CdO nanoflake arrays on ZnO nanorod arrays for efficient detection of diethyl ether. Issue 3 (6th January 2016) - Ban, Sheng-Guang; Liu, Xiao-Hua; Ling, Tao; Dong, Cun-Ku; Yang, Jing; Du, Xi-Wen
Abstract : A double layer structure, CdO porous nanoflake arrays on ZnO nanorod arrays, was fabricated and achieved excellent gas-sensing performance upon exposure to diethyl ether. Abstract : We report the template synthesis and gas detection of CdO porous nanoflake arrays (P-NFAs) on ZnO nanorod arrays. The P-NFAs possesses a large surface-to-volume ratio, high-energy exposed surface, unimpeded channels for gas flow, and hierarchical holes. As a result, the device exhibits excellent sensing properties upon exposure to diethyl ether.